The effects of circuit training versus high-intensity interval training on the endurance of volleyball athletes: a randomized controlled trial - Francesca Latino; Nugroho Susanto; Khoiril Anam; Hendra Setyawan; Emma Saraiello; Francesco Tafuri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Despite its intermittent nature, volleyball places significance on a high aerobic capacity, particularly evident in multiset games that demand sustained high-performance levels. Various training approaches exist to enhance the endurance of volleyball athletes. Thus, the fundamental aim of this research is to examine the contrasting effects of utilizing high-intensity interval training (HIIT) and circuit training methods to enhance volleyball athletes' endurance. The study used an Experimental group that partook in a HIIT training regime, and a Contrast group that undertook a Circuit training program. Thirty male volleyball players aged between 17 and 22 years (M=19.14; SD±1.61) were purposefully selected for the study and split into Contrast and Experimental groups of 15 each. At the beginning and end of the intervention programs both groups underwent physiological assessments for Maximum Oxygen Consumption (VO2max), Heart Rate Recovery (HRR), Peak Inspiratory Flow (PIF), Peak Expiratory Flow (PEF), and Force Vital Capacity (FVC). As result a meaningful Time x Group interaction for the VO2max, HRR, PIF, PEF and FVC was observed. This represents a significant improvement in the treatment group (p < 0.001). No material change was observed in the comparison group. Findings revealed that the HIIT training approach outperformed the circuit training method in enhancing volleyball athletes' endurance. Consequently, it is should be beneficial for volleyball players to incorporate HIIT into their standard training regimens.